Counselor Adaptation to the Impact of Social Media on Students' Mental Health and Identity - Zikry Latupasjana; Hanisa Afrianti; Mauna Tasya Siregar; Muhammad Wahbi Wido; Niken Novia Fitri (Program Studi Bimbingan Konseling, Fakultas Tarbiyah dan Ilmu Keguruan UIN Bukittinggi, 2025)
The omnipresent nature of social media in university students' daily experiences has generated unprecedented challenges for mental health professionals in higher education environments. This research examines how counselors modify their methodologies to respond to social media's evolving influence on student psychological wellbeing and identity development. Utilizing semi-structured interviews with 42 university counselors throughout Southeast Asia alongside quantitative data from 215 student surveys, this study identifies critical adaptation techniques that strengthen counseling effectiveness in contemporary digital contexts. Results indicate that effective counselors implement comprehensive strategies including: enhancing technological competency, incorporating specialized social media evaluation instruments, developing targeted intervention frameworks, and advocating digital health practices. The data demonstrates that counselors who successfully adapt their approaches achieve higher student participation rates and superior outcomes when addressing social media-related psychological distress. This research expands the emerging knowledge base regarding technology-informed therapeutic practices and establishes an adaptation framework for counselors that integrates conventional counseling methodologies with essential digital-era skills